Halal Products Assurance Policy Model and Its Impact on Sustainability of Fish Ball SMI using System Dynamics Simulation Approach - Dwi Iryaning Handayani; Haryono Haryono; Tri Prihatiningsih (Industria: Jurnal Teknologi dan Manajemen Agroindustri, 2020)
Abstract Indonesian government requires all products distributed and traded in Indonesian territory are halal certified. However, the ability of Small and Medium Industries (SMI) to implement this law of halal product assurance is relatively low. For this reason, it is crucial to review the application of halal assurance policy on the sustainability of fish ball SMI since fish ball grinding process is usually performed in public places, so that it is relatively risky to be contaminated with non-halal product. The objective of this research is to establish halal product assurance policy model and its impact on the sustainability of fish ball SMI. The approach used to review SMI policy and sustainability model was system dynamics simulation method supported by Vensim™ software. System Dynamics simulation generates two scenarios; the first scenario was fish ball SMI that applies halal assurance, and the second scenario was fish ball SMI that does not apply halal assurance and standard under the competitor. The simulation result showed that halal assurance gives better market share value that leads to the increasing operational cost variable, followed by the significant increase of business cash and better sustainability in the business. Therefore, the SMI actors will be able to comprehensively understand their obligation to comply with the government regulation which stated that all products distributed in Indonesia are required to have halal certification and it should be able to keep the sustainability of fish ball SMI.Keywords: system dynamics, halal control point, model, policy, sustainability